Assessment of the third finger middle phalanx maturation stages: A study of repeatability and diagnostic agreement - Perinetti, Giuseppe; Tecco, Simona; Primozic, Jasmina (South European Journal of Orthodontics and Dentofacial Research (SEJODR), 2022)
Data regarding the repeatability of the third finger middle phalanx maturation (MPM) method is still lacking. This study evaluated both the repeatability and diagnostic accuracy of the visual assessment of the MPM stages. Ten operators were given detailed instructions of the 5-stage MPM method and were asked to stage 80 cases, which included radiographs of equal number of all 5 MPM stages. Radiographs of the third finger were created by cropping hand-wrist radiographs of the Burlington Growth Study, ensuring the inclusion of several borderline cases. Such assessment was repeated in two sessions (T1 and T2) 4 weeks apart. For both the sessions, overall agreement and kappa coefficients were above 80% and 0.86, respectively. Most of the disagreements were seen for stages 1 and 2 with overall mean scores between the sessions being 29.7% and 39.4%, respectively. With only 4 exceptions (out of over 1,600 recordings), 1-stage apart disagreements were seen. Overall diagnostic accuracy ranged from 83.7% for MPM stage 2 (T1) to 99.3% for MPM stage 5 (T1). The MPM method has a satisfactorily level of repeatability and diagnostic agreement. About 1 case out of 5 remains misclassified, disagreement is mostly limited to 1-stage apart, with stage 2 being the most critical.